Wpływ traktatu lizbońskiego na europejskie partie polityczne - Beata Kosowska‑Gąstoł (Ksiegarnia Akademicka Publishing, 2019)
Impact of the Lisbon Treaty on European Political Parties The subject of the article is to analyze the relevant provisions of the Lisbon Treaty in order to show the changes they have introduced for Europarties. The main thesis of the article is that even if the direct influence of the said Treaty on Europarties was negligible, its indirect impact could be significantly greater. The article has been divided into three parts. The first recalled the genesis of the Europarties and outlined the legal framework for their activities until the entry into force of the Treaty of Lisbon. In the second one – the provisions of the Treaty directly devoted to the Europarties were analyzed. The third part depicted the areas in which – by adopting a specific interpretation of the Treaty provisions – the Europarties may try to exert an indirect influence on the EU decision‑making process, especially a new way of selecting the President of the European Commission.